2011
DOI: 10.1038/emboj.2011.139
|View full text |Cite
|
Sign up to set email alerts
|

AT1R-CB1R heteromerization reveals a new mechanism for the pathogenic properties of angiotensin II

Abstract: The mechanism of G protein-coupled receptor (GPCR) signal integration is controversial. While GPCR assembly into hetero-oligomers facilitates signal integration of different receptor types, cross-talk between Gai-and Gaqcoupled receptors is often thought to be oligomerization independent. In this study, we examined the mechanism of signal integration between the Gai-coupled type I cannabinoid receptor (CB 1 R) and the Gaq-coupled AT1R. We find that these two receptors functionally interact, resulting in the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
148
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(156 citation statements)
references
References 50 publications
6
148
2
Order By: Relevance
“…Furthermore, it is likely that the ability of pERK1/2 to inhibit (Bell-Horner et al, 2006) and pAkt to enhance (Wang et al, 2003) GABA neurotransmission explains, at least partly, our recent findings that implicated central GABA inhibition in the central CB 1 Revoked pressor response (Ibrahim and Abdel-Rahman, 2011). The present and reported findings suggest that CB 1 R-evoked ERK1/2 activation is a complex process and might involve other systems such as orexins, angiotensin II, and dopamine (Valjent et al, 2001;Hilairet et al, 2003;Ellis et al, 2006;Rozenfeld et al, 2011). For instance, tetrahydrocannabinolevoked ERK1/2 activation in the striatum was abolished by prior dopamine receptor blockade (Valjent et al, 2001).…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, it is likely that the ability of pERK1/2 to inhibit (Bell-Horner et al, 2006) and pAkt to enhance (Wang et al, 2003) GABA neurotransmission explains, at least partly, our recent findings that implicated central GABA inhibition in the central CB 1 Revoked pressor response (Ibrahim and Abdel-Rahman, 2011). The present and reported findings suggest that CB 1 R-evoked ERK1/2 activation is a complex process and might involve other systems such as orexins, angiotensin II, and dopamine (Valjent et al, 2001;Hilairet et al, 2003;Ellis et al, 2006;Rozenfeld et al, 2011). For instance, tetrahydrocannabinolevoked ERK1/2 activation in the striatum was abolished by prior dopamine receptor blockade (Valjent et al, 2001).…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, CB 1 Rs have been shown previously to interact with other G protein-coupled receptors, including dopamine D 2 receptors (which promotes a switch in the preferential coupling from G i to G s ) (27), D 2 receptors and adenosine A 2A receptors simultaneously (producing a negative modulation of D 2 receptor function by A 2A and CB 1 R agonists) (28), opioid receptors (which produces a negative cross-talk between protomers) (29), orexin OX 1 receptors (eliciting a positive cross-talk in response to orexin and cross-antagonism) (30), and angiotensin AT 1 receptors (resulting in the potentiation of AT 1 receptor signaling) (31). More recently, coimmunoprecipitation assays in HEK293 cells have suggested that CB 1 R can form heteromers with GPR55 (32).…”
Section: Discussionmentioning
confidence: 99%
“…Other dramatic examples of functional selectivity in receptor heteromers are changes in G protein coupling, such as with the angiotensin AT 1 -cannabinoid CB 1 receptor heteromer (Rozenfeld et al, 2011). Although, in the normal liver angiotensin AT 1 receptor signals via G q , under conditions of alcohol-induced liver fibrosis cannabinoid, CB 1 receptor is upregulated and heteromerizes with angiotensin AT 1 receptor and this, in turn, leads to G i -mediated signaling by angiotensin AT 1 receptor that can be blocked by cannabinoid CB 1 receptor antagonist, suggesting that AT 1 -CB 1 receptor heteromer represents a disease-specific and potentially tissue-specific therapeutic target.…”
Section: Allosterism In Receptor Oligomers: Allosteric Modulation mentioning
confidence: 99%